2021
DOI: 10.1152/ajpcell.00425.2020
|View full text |Cite
|
Sign up to set email alerts
|

P110α and P110δ catalytic subunits of PI3 kinase regulate lysophosphatidylcholine-induced TRPC6 externalization

Abstract: Lipid oxidation products, including lysophosphatidylcholine (lysoPC) inhibit endothelial cell (EC) migration in vitro and impair EC healing of arterial injuries in vivo, in part by activating phosphatidylinositol 3-kinase (PI3K), which increases the externalization of canonical transient receptor potential 6 (TRPC6) channels and the subsequent increase in intracellular calcium. Inhibition of PI3K is a potential method to decrease TRPC6 activation and restore migration, but PI3K is involved in multiple intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…However, the Ca 2+ -dependent proteinase calpain seems to be a master effector serving multiple Ca 2+ signaling pathways. In addition to SOCE pathway reported by the present study, both TRPC5 and TRPC6 Ca 2+ signals also activate calpain pathway (36,37,52). Thus, Ca 2+ signals from different sources in podocytes may interact with each other at a site of a particular signaling pathway.…”
Section: Discussionsupporting
confidence: 56%
“…However, the Ca 2+ -dependent proteinase calpain seems to be a master effector serving multiple Ca 2+ signaling pathways. In addition to SOCE pathway reported by the present study, both TRPC5 and TRPC6 Ca 2+ signals also activate calpain pathway (36,37,52). Thus, Ca 2+ signals from different sources in podocytes may interact with each other at a site of a particular signaling pathway.…”
Section: Discussionsupporting
confidence: 56%
“…Lysophosphatidylcholine (lysoPC), a bioactive phospholipid generated by various biological processes, is abundant in plasma and accumulates in damaged blood vessels [ 18 , 19 ]. Previous studies have demonstrated that its inhibition of vascular endothelial cell function is unfavorable for the restoration of endothelial integrity after injury [ 20 , 21 ]. Moreover, studies have shown that lysoPC is associated with the activation of endothelial NLRP3 inflammasomes [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biological functions of lysoPC vary among cell types, promoting atherosclerotic plaque formation and inflammatory reaction, enhancing anti‐infection response, regulating blood glucose and affecting tumour invasion and metastasis 55 . LysoPC inhibited endothelial cell migration and healing of arterial injuries partially through the activation of PI3K p110α and p110δ isoforms and promoted phagosome maturation and production of inflammatory mediators through PI3K and p38MAP 56,57 . LysoPC activated the ERK pathway to regulate the production of ROS and Ca ++ in mitochondria 58 .…”
Section: Discussionmentioning
confidence: 99%
“… 55 LysoPC inhibited endothelial cell migration and healing of arterial injuries partially through the activation of PI3K p110α and p110δ isoforms and promoted phagosome maturation and production of inflammatory mediators through PI3K and p38MAP. 56 , 57 LysoPC activated the ERK pathway to regulate the production of ROS and Ca ++ in mitochondria. 58 In lung cancer cells, lysoPC could elevate mRNA and protein expression of PI3K‐ and ERK‐signal pathways associated with 10 kinases in lysoPC‐treated cells, presenting multi‐kinase‐based molecular mechanisms (Figure S6I,J ).…”
Section: Discussionmentioning
confidence: 99%